Impactos da certificação Utz Kapeh no sistema de informação e na gestão de duas empresas produtoras de café, no Sul de Minas Gerais - Martinez, João Roberto Lo Turco (2008)
The objective of this dissertation was pointing the impacts of certification of coffee in the information systems, in people, management and competitiveness of two rural producers of coffee in the process of certification Utz Kapeh, as well as pointing the impacts of changes in the information system of these companies in people, management and the advantages / disadvantages of these changes, on the point of view of its managers. For this reason, were used analytical techniques and analysis of content. Of the results, was evident that achieving certification Utz Kapeh is an advantage because of helping the company to take a more professional management. The use of an information system to facilitate and organize the process of traceability is one of the things that most contributes to the improvement in management. However, adopting the certification does not guarantee different prices. In this study, drew up a model, which show a greater impact of certification in the management of organizations and the importance of a network (cooperative), as a way of obtaining a price differential for coffee certification and increase competitiveness. It point also to the changes related to people and the information system. KEY WORDS: certification, information system, management, competitiveness, coffee.